A novel mutation in the MYO7A gene is associated with Usher syndrome type 1 in a Chinese family. (August 2017) - He, Xiaoguang; Peng, Qi; Li, Siping; Zhu, Pengyuan; Wu, Chunqiu; Rao, Chunbao; Lin, Jingqi; Lu, Xiaomei
Abstract: Objectives: We aimed to investigate the genetic causes of hearing loss in a Chinese proband with autosomal recessive congenital deafness. Methods: The targeted capture of 159 known deafness genes and next-generation sequencing were performed to study the genetic causes of hearing loss in the Chinese family. Sanger sequencing was employed to verify the variant mutations in members of this family. Results: The proband harbored two mutations in the MYO7A gene in the form of compound heterozygosity. She was found to be heterozygous for a novel insertion mutation c.3847_3848 ins TCTG (p.N1285LfsX24) in exon 30 and for the known mutation c.2239_2240delAG (p.R747S fsX16)in exon 19. The novel mutation was absent in the 1000 Genomes Project. These variants were carried in the heterozygous state by the parents and were therefore co-segregated with the genetic disease. Clinical re-assessment, including detailed audiologic and ocular examinations, revealed congenital deafness and retinitis pigmentosa in the proband. Collectively, the combination of audiometric, ophthalmologic and genetic examinations successfully confirmed the phenotype of Usher syndrome type 1 (USH1). Conclusion: This study demonstrates that the novel mutation c.3847_3848insTCTG (p. N1285LfsX24) in compound heterozygosity with c.2239_2240delAG in the MYO7A gene is the main cause of USH1 in the proband. Our study expands the mutational spectrum of MYO7A and provides a foundation for further investigations elucidating the MYO7A -related mechanisms of USH1.